A New Look at the Corporate Social–Financial Performance Relationship - Wang, Heli; Choi, Jaepil (Journal of Management, 2013)
The authors develop the argument that the establishment of good stakeholder relations is influenced not only by a firm’s having a high level of corporate social performance but also by its ability to deliver consistent social performance. Therefore, both level and consistency in corporate social performance should have significant financial implications. More specifically, the authors suggest that level and two types of consistency in corporate social performance—temporal consistency and interdomain consistency—interact positively to influence a firm’s financial performance. Using a sample of 622 firms and 2,365 firm-year observations based on the Kinder, Lydenberg, Domini, & Co. data, the authors found empirical results supporting this argument. In addition, they found that maintaining consistently good social performance is more important for firms with high levels of knowledge intensity.